Antimicrobial Effects and Active Compounds of the Root of Aucklandia Lappa Decne (Radix Aucklandiae) - Cai, Xuewei; Yang, Chunping; Qin, Guangwei; Zhang, Min; Bi, Yan; Qiu, Xiaoyan; Lu, Liya; Chen, Huabao (Frontiers in Chemistry, 2022)
The development of new biological fungicides using plant metabolites has become an important direction for pesticide development, and previous studies found that Radix Aucklandiae had a certain inhibitory effect on plant pathogens. In this study, we systematically studied the antimicrobial activity of extracts of Radix Aucklandiae, and the active compounds were isolated, purified and structurally identified. Ethanol extracts of Radix Aucklandiae had different inhibitory effects on 7 common plant-pathogenic fungi, with EC50 (concentration for 50% of maximal effect) values ranging from 114.18 mg/L to 414.08 mg/L. The extract at concentration of 1000 mg/L had a significant control effect on strawberry grey mould and wheat powdery mildew of more than 90%. Three active compounds were isolated and purified from the extract, which were identified as alantolactone, dehydrocostus lactone and costunolide. All three compounds showed significant inhibitory effects on Botrytis cinerea, and the MIC (minimum inhibitory concentration) values were 15.63 mg/L, 3.91 mg/L and 15.63 mg/L. Dehydrocostus lactone also showed obvious inhibitory effect on Fusarium graminearum with an MIC value of 62.25 mg/L. The extract of Radix Aucklandiae has high antimicrobial activity against some common plant-pathogenic fungi, and the work lays a foundation for the development of extracts of Radix Aucklandiae as botanical fungicides.